2005
DOI: 10.1074/jbc.m413223200
|View full text |Cite
|
Sign up to set email alerts
|

Type I Transforming Growth Factor β Receptor Binds to and Activates Phosphatidylinositol 3-Kinase

Abstract: We have examined the interaction of transforming growth factor (TGF)␤ receptors with phosphatidylinositol 3-(PI3) kinase in epithelial cells. In COS7 cells, treatment with TGF␤ increased PI3 kinase activity as measured by the ability of p85-associated immune complexes to phosphorylate inositides in vitro. Both type I and type II TGF␤ receptors (T␤R) associated with p85, but the association of T␤RII appeared to be constitutive. The interaction of T␤RI with p85 was induced by treatment with TGF␤. The receptor as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 34 publications
6
144
0
4
Order By: Relevance
“…PI3K function is also required for TGF-b-mediated EMT and cell migration (Bakin et al, 2000). The TGF-b type-1 receptor (ALK5) can bind to p85, the regulatory subunit of PI3K, and activate the PI3K pathway (Yi et al, 2005). Our study showed that HAb18G/CD147 expression was driven by the TGF-b/PI3K/Akt pathway, which exerted resistance to apoptosis.…”
Section: Cell Linesmentioning
confidence: 70%
“…PI3K function is also required for TGF-b-mediated EMT and cell migration (Bakin et al, 2000). The TGF-b type-1 receptor (ALK5) can bind to p85, the regulatory subunit of PI3K, and activate the PI3K pathway (Yi et al, 2005). Our study showed that HAb18G/CD147 expression was driven by the TGF-b/PI3K/Akt pathway, which exerted resistance to apoptosis.…”
Section: Cell Linesmentioning
confidence: 70%
“…Both TbRII and Alk5 have been shown to associate indirectly with p85. Although the association of p85 with TbRII is constitutive, the Alk5-p85 interaction is ligand-dependent (Yi et al, 2005). TGFb-mediated cell motility and protection from apoptosis are blocked by LY294002 and/or expression of dominant-negative Akt (Bakin et al, 2000;Shin et al, 2001;Horowitz et al, 2004;Muraoka-Cook et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In transformed cells, treatment with TGFb enhances survival via Akt-induced phosphorylation of FKHRL1 (Shin et al, 2001). TGFb has been shown to activate PI3K and its target Akt (Higaki and Shimokado, 1999;Bakin et al, 2000;Yi et al, 2005). Although the signaling programs regulating TGFb-mediated protection from cell death are not completely understood, this protection is blocked by the PI3K inhibitor LY294002 and/or expression of dominantnegative Akt (Shin et al, 2001;Horowitz et al, 2004;Muraoka-Cook et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, T␤RI activates ERK by directly phosphorylating ShcA (27). PI3 kinase associates indirectly with T␤RI (66), and TGF-␤ 1 -induced Akt phosphorylation occurs independently of Smads in fibroblasts (60). Transactivation of the EGF receptor (EGFR) by TGF-␤ 1 can also stimulate PI3 kinase and Akt (22,36,37,52).…”
Section: Discussionmentioning
confidence: 99%